A pharmacokinetic and pharmacogenetic evaluation of contraceptive implants and antiretroviral therapy among women in Kenya and Uganda. (1st November 2019) - Patel, Rena C.; Stalter, Randy M.; Thomas, Katherine K.; Tamraz, Bani; Blue, Steven W.; Erikson, David W.; Kim, Christina J.; Kelly, Edward J.; Nanda, Kavita; Kourtis, Athena P.; Lingappa, Jairam R.; Mugo, Nelly; et al.
Abstract : Objectives: To evaluate pharmacokinetics and pharmacogenetics of contraceptive implant progestin concentrations in HIV-positive women initiating efavirenz (EFV)-containing or nevirapine (NVP)-containing antiretroviral therapy (ART). Design: We analyzed stored samples from women self-reporting implant use in the Partners PrEP Study. Methods: Plasma samples collected every 6 months were analyzed for levonorgestrel and etonogestrel concentrations. Progestin concentrations from samples collected after ART initiation were compared with pre-ART concentrations for intraindividual comparisons. We used adjusted linear mixed models to compare hormone concentrations between individuals on EFV and NVP to a no ART group. We then evaluated whether possessing certain alleles with known or possible influences on EFV, NVP, or progestin metabolism were associated with changes in progestin concentrations or modified the association between ART use and progestin concentrations. Results: Our analysis included 11 women who initiated EFV, 13 who initiated NVP, and 36 who remained ART-naive. In the EFV group, the adjusted geometric mean ratio (aGMR) of levonorgestrel was 0.39 [90% confidence intervals (0.31, 0.49); P  < 0.001] and the etonogestrel aGMR was 0.51 (0.34, 0.76; P  = 0.006) compared with the control group. No difference was observed in the NVP group compared with controls [levonorgestrel 0.93 (0.74, 1.18); P  = 0.64; etonogestrel 1.07 (0.77, 1.50); P  = 0.73]. Possession of four allele variants were found to result in further reductions in progestin concentrations among those receiving EFV. Conclusion: Concomitant use of EFV significantly reduces levonorgestrel or etonogestrel concentrations by 61 and 49%, respectively, compared with no ART use. We also report allelic variants in hepatic enzymes that influenced the extent of the observed drug-interaction between progestins and EFV.